Sharing approaches in collective self-consumption systems: A techno-economic analysis of the Spanish regulatory framework - Villalonga Palou, Joan Tomás; Serrano González, Javier; Riquelme Santos, Jesús Manuel; Álvarez Alonso, César; Roldán Fernández, Juan Manuel (Elsevier Ltd, 2023)
This paper proposes an analysis of the current regulatory framework for collective self-consumption in Spain. This regulatory framework proposes a model based on constant distribution coefficients for the allocation of self-consumed energy,as well as a constant distribution for the allocation of economic rights corresponding to surplus energy. The main advantage of this model is its simplicity and ease of implementation. Nonetheless,it has the disadvantage that part of the energy produced cannot be used (in economic terms) by the participants in the shared self-consumption system,which limits the economic potential of these facilities and therefore makes them less attractive to new investors. Therefore,this work proposes a techno-economic analysis of the influence of the current regulatory framework for collective self-consumption on the profitability of this type of projects. The analysis shows that,regardless of its simplicity of implementation,the existing scheme is not fully efficient,as part of the self-generated energy is not allocated to the community's consumption or surplus. This means that investors in the project obtain a profitability lower than the real potential of the installation. Furthermore,following the analysis carried out,an alternative distribution scheme is proposed that considerably improves the profitability of this type of projects. © 2023
Keywords: Economic analysis; Profitability; 'current; Consumed energy; Distribution coefficient; Model-based OPC; Prosumer; Regulatory frameworks; Renewable energy community; Self-consumption; Techno-Economic analysis; Power markets; Electricity markets; Prosumer; Renewable energy communities; Self-consumption; 25 Ciencias de la Tierra y del Espacio; ODS 7 - Energía asequible y no contaminante; ODS 9 - Industria, innovación e infraestructura; ODS 13 - Acción por el clima; ODS 11 - Ciudades y comunidades sostenibles